Biennale Interieur 2018 : Uw Interieur Gids. - Creve, Leen; Van Den Storm, Dieter; Nguyen, Mathieu; Moens, Hanna; Rombauts, Amélie; De Smet, Dennis (Kortrijk : Interieur Biënnale, 2018)
Stynen, Léon ; Willems, Conrad ; Delbart, Frederik ; Marcelis, Sabine ; Rylant, Inge ; Kerkhofs, Bram
boek